an Antioxidant Activities of Urena lobata L. Ethanolic Extract by DPPH Method: Uji Aktivitas Antioksidan Ekstrak Etanol Bunga Pulutan (Urena lobata L) Menggunakan Metode DPPH - Athiah Masykuroh; Saufa Hidayati (Jurnal Komunitas Farmasi Nasional, 2023)
Antioxidants are compounds that have a molecular structure that can provide electrons to free radical molecules and break free radical reaction chains. The purpose of this study was to determine the estimated content of secondary metabolites from Urena Lobata L. flowers ethanolic extract by phytochemical screening method and their antioxidant activity by DPPH (2,2-diphenyl-1-picrylhydrazil) method. Determination of the antioxidant activity of Urena Lobata L. flowers was carried out by observing the absorbance measured at a maximum wavelength of 516.40 nm and extract concentrations of 20 ppm, 40 ppm, 60 ppm, 80 ppm, and 100 ppm and then calculating the IC50 value. The results of the phytochemical screening test showed that the ethanol extract of pulutan flowers contained phenols, alkaloids, flavonoids, terpenoids, tannins and saponins. The results of the antioxidant activity test showed an average IC50 value of 5.337 ppm means it was categorized as a very strong antioxidant.